THE LEGAL PROTECTION FOR CHILDREN AS VICTIMS OF CRIMES OF THE SEXUAL VIOLENCE IN MAKASSAR CITY - Nurfadillah Herman; Hambali Thalib; Abdul Qahar (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal